Prevalence and Asscociated Factors of Ovarian Cyst Malignancy: A Cros-sectional Based Study in TSHRIEN UNIVERSITY HOSPITAL in LATAKIA - سلوم, نهاد; حسن صالح,; أحمد عبد الرحمن, (Latakia University Journal -Medical Sciences Series, 2024)
Ovarian cyst is the sac-like formation filled with brownish fluid and sebum in the ovarium. Most ovarian cysts are benign, and the potential to develop malignancy is only 2%. The malignant cyst is considered as cancer type. This study aimed to analyze the prevalence and associated factors of ovarian cyst malignancy. Methods: This crossectional based study used252 samples of women with an ovarian cyst in TSHIREN UNIVERSITY HOSPITAL . The detection of ovarian cyst is conducted by ultrasound and histopathological examination to determine the level of malignancy. Results: From 252 cases, there were9 cases of ovarian cyst malignancy (3.6%). There was a significant difference in the level of malignancy based on age (p= 0.000). The ovarian cyst in patients over 50 years old was more likely to develop into a malignant cyst. The majority of ovarian cysts subtype were bilateral cyst and endometriosis cysts, consist of 93 patients (36.9%) and 66 patient (26.2%) respectively. Analysis for the cyst location, majority of ovarian cysts was located bilaterally consist of 141 patients (56.0%). All patients with malignant cyst were not experience bleeding. There were no significant differences on category of cyst (p= 0,674), location of cyst (p= 0.294) and the presence of bleeding (p= 0.541) . Conclusion: The prevalence rate of ovarian cyst malignancy was 3.6% with age as a significantly associated factor